(untitled) (Journal of Foreign Language Studies, 2022)
The study was conducted to investigate the frequency of using metacognitive reading strategies (MRS) by the third-year English-majored students at the Faculty of Foreign Languages (FFL), Hanoi University of Industry (HaUI). To meet the research objectives, an online survey questionnaire was administered to 80 HaUI third-year English-majored students. Besides, two interviews with ten third-year English-majored students and three instructors in the Reading 5 course were also carried out. The findings showed that the students used the MRS with a medium frequency and employed the pragmatic reading strategies (PRS) more often than analytic reading strategies (ARS). This paper is hoped to provide a valuable reference for instructors and students to have deeper understanding about reading strategies, particularly MRS, thereby improving students’ reading skills.